(untitled) (Nepalese Journal of Development and Rural Studies, 2021)
Mother’s Group is one of the basic groups for women empowerment. It has been functioning for women’s empowerment and social development. Mothers group has managed many skill development programs, income generating programs, literacy programs etc which helped them to make independent. Mother’s group, self-help groups (SHG) and community-based organizations (CBO) play a vital role towards women empowerment by providing vocational trainings, training for self-employment, protection for women and self-awareness programs. Thus, they are mainly concerned with the upliftment of the women in the society. Empowerment of women has been a topic discussed at length in recent times and many strategies have been implemented to address enhance women’s condition. This paper seeks to explore some measure that should be adopted in order to position rural women as equal players in entrepreneurship and economic development. This paper discusses upon the empowerment of rural women by means of self-help group or mother’s group and the advantages of such groups among the rural women.